Can web-based tools measure logical thinking skills among university students - Hassan, Aminuddin; Mat Rashid, Abdullah (Macrothink Institute, 2015)
Web-based has a considerable influence in the methodology of the study. The use of web-based requires the internet connection. In general, technology is booming now and all people require internet to do any work. This paper is to examine whether the web-based tool can explore the level of logical thinking skills among university students. In the current curriculum of schools and universities, there is a lack of the inculcation of logical thinking skills. This paper begins by explaining the definition of logical thinking. Then, this paper describes the logical thinking from the perspective of philosophy. In addition, logical thinking also described from the viewpoint of Islam from this paper. This paper also discusses web-based, the advantages of using web-based and how to use web-based to in measuring students’ logical thinking skills.